Changes in the life of people with acquired spinal cord injury - Schoeller, Soraia Dornelles (2012)
ABSTRACTSpinal cord injury is a serious and incapacitating physical impairment with a strong personal and social impact. The general objective of this study was to understand what impacts the spinal cord injury has on the lives of those affected. The study also investigated some characteristics of the individuals, the performance of activities of daily living, life before the injury and the resources sought at the moment of the injury. This is a qualitative, exploratory and descriptive study. The participants were individuals living with spinal cord injury for over two years. Data were collected using semi-structured interviews. The study results showed that the individuals divide their lives into before, during, and after the injury, reliving the causal moment continuously. The family is essential to the individual’s (re)adaptation. Nurses must improve their knowledge regarding spinal cord injury in order to support the individual, their family and the health care team.Descriptors: Nursing Care; Rehabilitation; Spinal Cord Injuries.